Assessment of the Effectiveness of Surgical Treatment of Lumbar Spinal Stenosis - Melenko, V.I. (TERRA ORTHOPAEDICA, 2024)
Summary. Background. Lumbar spinal stenosis, which is one of the main causes of disability in older patients, occurs in countries with different levels of income. There has been a surge of endoscopic procedures in recent years, which requires further study. Objective: to compare the results of surgical treatment of lumbar spinal stenosis of patients operated on using different methods. Materials and Methods. Data from examination and treatment of patients (n=43) who underwent surgical intervention for lumbar spinal stenosis. In the clinical part, the following methods were used: pain intensity was assessed using the visual analogue scale (VAS, cm); patients’ satisfaction and quality of life were assessed using the Oswestry Low Back Pain Questionnaire – Oswestry Disability Index (ODI). The Oswestry Questionnaire (version 2.0) allowed us to determine the level of impairment in the quality of life of patients in points and as a disability index. Results. In group I (UBE/ULBD), the index of back pain before surgery was 5.3±1.3, in group II (open decompression) it reached 5.8±1.4 and in group III (decompressive laminectomy with transpedicular fixation) it was 5.5±1.1 cm (p>0.05). In the postoperative period, the index of back pain decreased in group I (UBE/ULBD) from 5.3±1.3 cm to 1.4±0.6 cm (p < 0.05), and improvement was observed within 6 months up to 0.5±0.3 cm (p < 0.05); in group II, the index decreased from 5.8±1.4 to 2.1±0.7 cm with positive dynamics over 6 months to 0.6±0.3 cm (p < 0.05); in group III, the level of pain after surgery remained relatively high (4.1±0.8), but there was an improvement to 1.2±0.9 (p < 0.05) within 6 months. The level of pain in the lower extremity in group I (UBE/ULBD) decreased from 4.7±1.1 cm to 2.3±1.0 cm and to 1.1±0.4 cm during 6 months of follow-up (< 0.05); in group II, the level of pain decreased from 5.1±1.2 cm to 1.1±0.9 cm, with improvement to 1.2±0.3 cm within 6 months (< 0.05); in group III, the pain index in the lower extremity before surgery was 5.1±1.2 cm and remained quite high (3.2±1.1 cm) in the early postoperative period and slightly higher (1.4±0.9) compared to other groups after 6 months (<0.05). Assessing the quality of life of patients, the following was found: group I showed positive dynamics, namely ODI improved from 52.7±19.8% before surgery to 10.7±5.4% after 6 months; in group II, ODI improved from 57.9±15.4% before surgery to 15.0±4.1% after 6 months; in group III, ODI was 51.2±16.6% before surgery and 20.3±8.1% after 6 months, which means that at the time of the last survey, patients with transpedicular fixation required additional rehabilitation interventions for recovery. Conclusions. Analysis of the data showed that the indicators of pain in the lower limbs and back, as well as the quality of life in the early and late follow-up periods slightly differed in group I (endoscopic decompression (UBE/UBLD)) and group II (open decompression), but significantly worsened in group III (decompression laminectomy with transpedicular fixation). Decompressive laminectomy with transpedicular fixation requires additional rehabilitation interventions for patients for full recovery.